Analisis Swot Pada Bauran Pemasaran Syariah Guna Merumuskan Strategi Kompetitif Pada NU Mart Carenang - Safari Safari; Moh. Mukhsin (Universitas 45 Surabaya, 2024)
SWOT analysis will be used to analyze NU Mart's internal and external factors. NU Mart has many competitors so NU Mart sales are still low. The aim of this research is to formulate a competitive strategy for the sharia marketing mix using SWOT analysis. This research uses a qualitative research method with a case study type of research. The data collection technique uses interviews with key informants, namely the directors of NU Mart and observation by looking and observing directly at the research object. From the research results, it was found that the position of NU Mart was in quadrant 1 with coordinates at the point [1.55:0.67]. Quadrant 1 position is a condition that supports aggressive strategies. This quadrant 1 position also supports the S-O (Strength-Opportunity) strategy. S-O strategies that can be implemented by NU Mart include: (1) Creating various kinds of promotions such as discount promos for NU residents, buy package promos, buy one get one free promos, end of month discounts and other promotions, (2) Intensify promotions especially to local residents both offline and online. (3) Improve service quality. (4) Opening a new branch in another location within the same sub-district.